The Role Of Sexuality Knowledge And Parent’s The Role Of Communication Quality In Introducing Sex Education To Adolescents - Ami Linda Kustati Kustati; Kartika Adyani; Friska Realita (Institute of Computer Science (IOCS), 2022)
Deviant behavior is the result of an imperfect socialization process. The group most frequently encountered with deviant behavior is adolescents. One form of adolescent deviant behavior is free sex, free sex is free sex is a problem from the lack of sexuality education, so there can be some problems as a result of free sex behavior in adolescents in the short term. Objective: to conduct a literature review on the role of knowledge of sexuality and the quality of communication between parents and children in introducing free sex education to adolescents. Methods: Results: Based on the results of the articles collected and the analysis of writing, it was found that knowledge of sexuality and the quality of parent-child communication is an important role in introducing free sex education where parents are very important in shaping their children's attitudes